Lignin as immobilization matrix for HIV p17 peptide used in immunosensing - Cerrutti, Bianca M. [UNESP]; Moraes, Marli L.; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (Elsevier B.V., 2015)
Immunosensors based on electrical impedance spectroscopy (EIS) are increasingly being used as a fast and potentially low cost method for clinical diagnostics. In this work we fabricated immunosensors by depositing layer-by-layer (LbL) films made with an antigenic peptide (p17-1) sequence (H2N-LSGGELDRWEKIRLRPGG-OH) and lignin on interdigitated gold electrodes, which could detect anti-p17 (HIV, human immune deficiency virus) antibodies (Ab) in phosphate buffered solutions (PBS). The molecular recognition interaction between the peptide (p17-1) and the specific Ab (anti-p17) yielded substantial changes in morphology of the with LbL films, with increased roughness according to atomic force microscopy data. This interaction is behind the high sensitivity of the immunosensor. Indeed, from the EIS results, we noted that the capacitance increased significantly with the specific Ab concentration, before getting close to saturation of available peptide sites at high concentrations. Concentrations of specific antibodies as low as 0.1 ng/mL could be detected and the immunosensors had their activity preserved for two months at least. The selectivity of the immunosensor was confirmed with two types of control experiments. First, no changes in impedance were observed when the lignin/peptide LbL immunosensor was immersed into a PBS solution containing the non-specific Ab (anti-HCV for Hepatitis C) antibodies. Furthermore, for sensing units made LbL films of lignin only, the electrical response was not affected by adding specific antibodies into the PBS buffer. The successful immunosensing for HIV with antigenic peptides in a lignin matrix is also relevant for valorization of lignin, which is an important biomass component in the sugar and ethanol industry, and brings the prospect for all-organic, biocompatible sensors if implantation is ever required. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Layer-by-layer films; Immunosensors; HIV; Lignin; Peptides; Impedance spectroscopy